2019
DOI: 10.1515/med-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and psychological symptoms in neurocognitive disorders: Specific patterns in dementia subtypes

Abstract: AbstractBackgroundBehavioural and psychological symptoms in dementia (BPSD) form an important sub-syndrome of dementia. We assessed the frequency and severity of BPSD in a random sample of Hungarian treatment-naïve dementia patients. Furthermore, we examined the relationship between cognitive symptoms and BPSD and the pattern of BPSD in specific types of dementias. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
13
0
4
Order By: Relevance
“…In our previous publication, the relationship between cognitive function and NPS was analysed in detail [ 18 ]. Therefore, this study’s focus is particularly on the relationship between NPS and quality of life, illness intrusiveness and caregiver’s burden.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous publication, the relationship between cognitive function and NPS was analysed in detail [ 18 ]. Therefore, this study’s focus is particularly on the relationship between NPS and quality of life, illness intrusiveness and caregiver’s burden.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to individual symptoms, based on frequency scores, abnormal motor behaviours (2.7 [SD = 1.2]), depression (1.8 [SD = 1.2]), agitation (1.7 [SD = 1.2]) and eating-appetite change (1.4 [SD = 1.3])were the most frequent in the total sample. The relationship between cognitive function and NPS is described in detail in our previously published article, "Behavioural and psychological symptoms in neurocognitive disordersspecific patterns in dementia subtypes"[18].…”
mentioning
confidence: 99%
“…On the other hand, certain degree of cognitive impairment may bias assessment of depressive symptoms, including that made by the BDI, through hindering the capacity of understanding the questions properly and of correct recollection of memories for the answers, or just simply not being able to concentrate long enough for a task [20]. The study of Majer et al [21] further underlined neccessity to be cautious when interpreting changes in cognition and mood of patients with metabolic syndrome and CSVD, as it demonstrated that worse cognitive functions in patients with dementia were related to higher frequency and greater severity of symptoms related to depression, like apathy, irritability, sleep-wake cycle dysfunctions and changes of appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты исследования R. Majer и соавт. [25] показали, что не только подтип деменции, но и уровень когнитивных нарушений связан с частотой и тяжестью некоторых НПС. Утяжеление когнитивного функционирования коррелирует с более высокой частотой и большей выраженностью апатии, раздражительности, нарушениями цикла сна и бодрствования, изменениями аппетита, аномальным двигательным поведением и расторможенностью.…”
Section: Discussionunclassified